Amorphous‐Confined Crystalline CuO Nanoflakes for Enhanced Ethylene Production from CO2 Electroreduction. Issue 4 (30th January 2023) - Zhao, Dandan; Zhang, Shaoyang; Guo, Tianyu; Zhao, Qiang; Du, Jianping; Li, Jinping
Abstract: The electrocatalytic reduction of CO2 to high value‐added chemicals is one of the effective technologies to achieve the goal of carbon neutralization. However, highly selective production of hydrocarbon via electrochemical conversion of CO2 still has great challenges. Herein, a unique CuO phase composition is constructed that consists of rectangular nanoflakes possessing crystalline/amorphous structures by the facile strategy. Crystalline CuO square nanoblocks are confined in amorphous nanoflakes and form crystalline/amorphous hybrid phase. The results of electrocatalytic CO2 reduction demonstrate that this crystalline/amorphous CuO material exhibits superior CO2 conversion ability with ethylene Faradaic efficiency of 58.3 % at −1.08 V vs. RHE, which is ascribed to nanoflake structures and fast electron transfer on the crystalline/amorphous interfaces because of superior conductivity of amorphous CuO. The present research provides an effective route to reconstruct novel crystalline/amorphous interfaces of CuO for catalysis applications. Abstract : Carbon dioxide reduction : The rectangular nanoflakes with crystalline/amorphous phase structures that the square nanoblocks are confined in amorphous nanoflakes efficiently enhance the electrocatalytic conversion of CO2 to ethylene.